Evaluasi Proses Amdal Sebagai Dasar Penerbitan Izin Lingkungan Dalam Rangka Mewujudkan Pembangunan Berkelanjutan Di Jawa Tengah - Agus Sriyanto (Jurnal Good Governance, 2018)
Any business activity having a significant impact on the environment shall have Amdal. The problem is the Amdal process is complicated and takes a long time. The objective of the study was to evaluate the Amdal process as the basis for the issuance of environmental permit on the Amdal Appraisal Commission, Central Java Province. The research method is descriptive qualitative through in-depth interviews, study documents, questionnaires and Focus Group Discussion (FGD). The conclusion of the research is the performance of the technical team of Amdal Appraisal Commission (KPA) of Central Java Province in assessing the Amdal is faster than the standard time set, while the performance of Amdal LPJP / individual consultant is very slow and less professional.